Effect of home-based, overground robotic-assisted gait training on vascular health in people with chronic stroke - Faulkner, James; Wright, Amy; Stone, Keeron; Fryer, Simon; Martinelli, Louis; Lambrick, Danielle; Paine, Eloise; Stoner, Lee (Frontiers in Neurology, 2023)
Overground robotic-assisted gait training (O-RAGT) has been shown to improve clinical functional outcomes in people living with stroke. The purpose of this study was to identify whether a home-based O-RAGT program, in combination with usual care physiotherapy, would demonstrate improvements in vascular health in individuals with chronic stroke, and, whether any changes in vascular outcomes would be sustained 3 months after completing the program. Thirty-four participants with chronic stroke (between 3 months and 5 years post-stroke) were randomized to either a 10-week O-RAGT program in combination with usual care physiotherapy, or to a usual care physiotherapy only control group. Participants' (n = 31) pulse wave analysis (PWA), and regional [carotid-femoral pulse wave analysis (cfPWV)] and local (carotid) measures of arterial stiffness were assessed at baseline, post-intervention, and 3-month post-intervention. Analysis of covariance demonstrated a significant reduction (improvement) in cfPWV between BL and PI for O-RAGT (8.81 ± 2.51 vs. 7.92 ± 2.17 m/s, respectively), whilst the control group remained unchanged (9.87 ± 2.46 vs. 9.84 ± 1.76 m/s, respectively; p < 0.05; ηp2 = 0.14). The improvement in cfPWV was maintained 3 months after completing the O-RAGT program. There were no significant Condition by Time interactions for all PWA and carotid arterial stiffness measures (p > 0.05). A significant increase in physical activity, as determined by the time spent stepping, was observed for O-RAGT between baseline and post-intervention assessments (3.2 ± 3.0–5.2 ± 3.3%, respectively) but not for CON (p < 0.05). The improvement in cfPWV, in combination with an increase in physical activity whilst wearing the O-RAGT and concomitant reduction in sedentary behavior, are important positive findings when considering the application of this technology for “at home” rehabilitation therapy for stroke survivors. Further research is needed to determine whether implementing “at home” O-RAGT programs should be a part of the stroke treatment pathway. Clinical trial registration https://clinicaltrials.gov, identifier NCT03104127.